2009
DOI: 10.1038/cgt.2009.22
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of PAK7, MAP3K7 and CK2α kinases inhibits the growth of MiaPaCa2 pancreatic cancer cell xenografts

Abstract: A panel of kinases whose inhibition increased apoptosis of pancreatic adenocarcinoma cells in vitro was recently established. The aim of this work was to observe in a mouse xenograft model whether inhibition of these kinases would alter pancreatic tumor growth. Rate of apoptosis, caspase-3 activity and cell viability were assessed in two pancreatic cancer cell lines, MiaPaCa2 and BxPC3, after inhibiting selected kinases by transfection of specific siRNAs. For in vivo experiments, MiaPaCa2 cells were injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
2
18
0
Order By: Relevance
“…However, the overexpression of PAK7 increases the migration and invasion of colon cancer cells in vitro . Our findings are consistent with other recent studies, which have identified an important role of PAK7 in tumorigenesis and metastasis of breast, pancreatic, and gastric cancer cells [21, 27, 28]. …”
Section: Discussionsupporting
confidence: 94%
“…However, the overexpression of PAK7 increases the migration and invasion of colon cancer cells in vitro . Our findings are consistent with other recent studies, which have identified an important role of PAK7 in tumorigenesis and metastasis of breast, pancreatic, and gastric cancer cells [21, 27, 28]. …”
Section: Discussionsupporting
confidence: 94%
“…As shown in Table S1, mRNA levels of a number of genes were significantly increased or decreased in microarray analyses after silencing of either ERK1 or ERK2 , and these patterns were confirmed in 13 selected genes using qRT-PCR (Figure 5). Several of these genes, including PAK7 or other members of this serine/threonine protein kinase family can directly activate MEK1 and inhibit cell transformation by preventing Ras-induced activation of ERKs 27, 28. Others such as BMP5 are activated via synergistic activation of Smad and p38 kinases and are differentially regulated during limb and tumor development 29.…”
Section: Discussionmentioning
confidence: 99%
“…5). Several of these genes including PAK7 or other members of this serine/threonine protein kinase family can directly activate MEK1 and inhibit cell transformation by preventing Ras‐induced activation of ERKs 27, 28. Others such as BMP5 are activated via synergistic activation of Smad and p38 kinases and are differentially regulated during limb and tumor development 29.…”
Section: Discussionmentioning
confidence: 99%